Clinically relevant depression in old age: An international study with populations from Canada, Latin America and Eastern Europe. (30th July 2016) - Ylli, Alban; Miszkurka, Malgorzata; Phillips, Susan P.; Guralnik, Jack; Deshpande, Nandini; Zunzunegui, Maria Victoria
Abstract: Our aim is to assess cross-national variations in prevalence of clinically relevant depression and to examine the relationships of social and health factors with depression in five diverse populations of older adults, from Canada, Brazil, Colombia and Albania. We used the data from the International Mobility in Aging Study. Clinically relevant depression was defined as a score of ≥16 on the Center for Epidemiologic Study Depression Scale (CES-D). Poisson regressions with robust covariance correction were used to estimate prevalence ratios associated with potential risk factors. Prevalence of clinically relevant depression across research sites varied widely, being consistently higher in women than in men. It was lowest in men from Brazil (6.3%) and highest in women from Albania (46.6%). Low education and insufficient income, living alone, multiple chronic conditions, and poor physical performance were all significantly associated with depression prevalence. Poor physical performance was more strongly associated with depression in men than in women. Similar factors are associated with clinically relevant depression among men and women and across research sites. The large variation in depression prevalence population rates is unexplained by the classical individual factors considered in the study suggesting the impact of country characteristics on depression among older populations. Highlights: We assess cross-national variations in prevalence of depression and examine the relationships of economic, social and health factors with depression in five diverse populations of older adults. Prevalence of depression across research sites varied widely, being consistently higher in women than in men. Low education and insufficient income, living alone, multiple chronic conditions, mobility disability, Activities of Daily Living disability, and poor physical performance were all significantly associated with depression prevalence. After adjustment for these factors, site differences remained. Depression prevalence was highest in Tirana and lowest in the two Canadian cities. Individual determinants of depression in old age are associated with social factors and poor health and disability but variations in population depression rates cannot be fully explained by these individual factors.